Answer:
Option D) h(x), f(x), g(x)
Step-by-step explanation:
we know that
The axis of symmetry of a vertical parabola is equal to the x-coordinate of the vertex of the parabola
Part 1) we have
[tex]f(x)=4x^{2} -1[/tex]
This is a vertical parabola open upward
The vertex is a minimum The vertex is the point (0,-1)
The x-coordinate of the vertex is 0
so
The axis of symmetry is x=0
Part 2) we have
[tex]g(x)=x^{2}-8x+5[/tex]
This is a vertical parabola open upward
The vertex is a minimum
Convert the equation into vertex form
[tex]g(x)-5=x^{2}-8x[/tex]
[tex]g(x)-5+16=x^{2}-8x+16[/tex]
[tex]g(x)+11=x^{2}-8x+16[/tex]
[tex]g(x)+11=(x-4)^{2}[/tex]
[tex]g(x)=(x-4)^{2}-11[/tex]
The vertex is the point (4,-11)
The x-coordinate of the vertex is 4
so
The axis of symmetry is x=4
Part 3) we have
[tex]h(x)=-3x^{2}-12x+1[/tex]
This is a vertical parabola open downward
The vertex is a maximum
Convert the equation into vertex form
[tex]h(x)-1=-3x^{2}-12x[/tex]
[tex]h(x)-1=-3(x^{2}+4x)[/tex]
[tex]h(x)-1-12=-3(x^{2}+4x+4)[/tex]
[tex]h(x)-13=-3(x+2)^{2}[/tex]
[tex]h(x)=-3(x+2)^{2}+13[/tex]
The vertex is the point (-2,13)
The x-coordinate of the vertex is -2
so
The axis of symmetry is x=-2
Part 4) Rank their axis of symmetry from least to greatest
1) h(x) -----> axis of symmetry -2
2) f(x) -----> axis of symmetry 0
3) g(x) -----> axis of symmetry 4
so
h(x),f(x),g(x)